Angiotensin II Impairs Glucose Utilization in Obese Zucker Rats by Increasing HPA Activity via an Adrenal-dependent Mechanism - Müller-Fielitz, H.; Raasch, W. (Hormone and Metabolic Research, 2013)
Angiotensin II (AngII) increases the activity of the hypothalamus-pituitary-adrenal (HPA) axis. We have previously demonstrated in obese Zucker rats (OZR) that AngII-induced HPA hyperreactivity was associated with impaired glucose utilization. The aim of this study was to specify the potential role of the adrenals in regulating AngII-dependent glucose homeostasis in obesity. Adrenal-specific AngII effects were determined regarding 1) the HPA axis by ACTH tests after treating OZR with AngII (9 μg/h, s.c.) for 3 months and 2) glucose utilization by oral glucose tolerance tests (OGTT) in OZR that were adrenalectomized (adx) or sham operated and treated for 1 month with AngII (9 μg/h, s.c.). AngII increased the corticosterone response after ACTH infusions, clearly indicating the key role of the adrenals for mediating stress reactions. Baseline levels of glucose and corticosterone were not altered by AngII treatment or by adrenalectomy. In contrast, AngII similarly reduced baseline insulin in sham and adxOZR. During OGTT, AngII increased glucose and corticosterone responses in shamOZR, whereas insulin was slightly diminished. This reaction pattern was lost when obese Zucker rats were adrenalectomized. In summary, we verified our hypothesis that the adrenal glands play a key role in worsening glucose homeostasis in obesity in response to AngII, which further supports recent findings that improvement in glucose utilization after AT1 blockade is related to reduced activity of the HPA axis.
Keywords: renin-angiotensin II system; obesity; insulin; stress; ACTH test; adrenalectomy